2023
DOI: 10.1002/ardp.202200654
|View full text |Cite
|
Sign up to set email alerts
|

2‐Phenylquinazolin‐4(3H)‐one scaffold as newly designed, synthesized VEGFR‐2 allosteric inhibitors with potent cytotoxicity through apoptosis

Abstract: New derivatives of 2-phenylquinazolin-4(3H)-one were designed, synthesized, and biologically evaluated as potent allosteric kinase inhibitors with in situ cytotoxicity against MCF-7 and HepG2 cells. Compounds 15 and 18 among the proposed compounds showed promising antiproliferative activity against MCF-7 (IC 50 = 1.35 µM) and HepG2 cells (IC 50 = 3.24 µM), comparable to sorafenib, with IC 50 values of 3.04, 2.93 µM, respectively, according to in situ cytotoxicity testing. Comparing compounds 15 and 18 to soraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…An in vitro VEGFR-2 enzyme assay showed that the latter five compounds, 29, 30, 31, 32a, and 32b significantly suppressed VEGFR-2 (IC50 = 0.290 ± 0.05, 0.517 ± 0.07, 0.380 ± 0.04, 0.377 ± 0.04, and 0.415 ± 0.03 µg/mL, respectively) compared to sorafenib, with an IC50 value of 0.588 µg/mL (Figure 13) [53]. In a recent study conducted by Elrayess et al [54], novel derivatives of 2-phenylquinazolin-4(3H)-one were developed. Their cytotoxic effects were assessed in situ against MCF-7 and HepG2 cells, revealing promising results.…”
Section: Vascular Endothelia Growth Factor Receptor (Vegfr) Inhibitorsmentioning
confidence: 81%
See 2 more Smart Citations
“…An in vitro VEGFR-2 enzyme assay showed that the latter five compounds, 29, 30, 31, 32a, and 32b significantly suppressed VEGFR-2 (IC50 = 0.290 ± 0.05, 0.517 ± 0.07, 0.380 ± 0.04, 0.377 ± 0.04, and 0.415 ± 0.03 µg/mL, respectively) compared to sorafenib, with an IC50 value of 0.588 µg/mL (Figure 13) [53]. In a recent study conducted by Elrayess et al [54], novel derivatives of 2-phenylquinazolin-4(3H)-one were developed. Their cytotoxic effects were assessed in situ against MCF-7 and HepG2 cells, revealing promising results.…”
Section: Vascular Endothelia Growth Factor Receptor (Vegfr) Inhibitorsmentioning
confidence: 81%
“…In a recent study conducted by Elrayess et al [ 54 ], novel derivatives of 2-phenylquinazolin-4(3 H )-one were developed. Their cytotoxic effects were assessed in situ against MCF-7 and HepG2 cells, revealing promising results.…”
Section: Quinazolines As Protein Kinases Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation